Adherence and long-term growth outcomes: results from the easypod™ connect observational study (ECOS) in paediatric patients with growth disorders. Issue 8 (August 2018) - Koledova, Ekaterina; Stoyanov, George; Ovbude, Leroy; Davies, Peter S W
Abstract : Objective: The easypod connect observational study (ECOS) assessed treatment adherence among paediatric patients receiving growth hormone (GH) via the easypod electronic injection device. Design: ECOS was an open-label, observational, longitudinal study conducted in 24 countries between 2010 and 2016, enrolling children treated with GH. Methods: The primary endpoint was the rate of treatment adherence during 5 years of follow-up. Impact of adherence on growth outcomes was assessed using Spearman's product–moment correlations. Results and conclusions: Overall, 1190 patients had easypod data available for ≥3 months; most patients had GH deficiency (75%); 606 of these patients were GH naïve at baseline. Over the first year of monitoring, the median rate of adherence was 93.7% among patients overall and >93.0% in GH-naïve patients, irrespective of the treatment indication. Clinically meaningful improvements in growth rates were observed after 1 year of treatment across all GH indications. Adherence decreased with increasing treatment duration, but the overall median adherence rate remained high after 3 years of follow-up: 87.2% ( n  = 409), 75.5% after 4 years ( n  = 143) and 70.2% after 5 years ( n  = 43). Statistically significant correlations between adherence and 1-year change in height standard deviation score ( P  < 0.001 for patients overall) and height velocity ( P  < 0.001) were observed. Conclusions: ECOS produced accurate, real-time adherence data in a large population of GH-treated children over 5 years of follow-up. Using the easypod connect system, physicians can potentially identify patients with inadequate adherence and poor response to treatment, enabling them to take appropriate action to help them maximise the benefits of GH treatment.